2022
DOI: 10.1002/anie.202208323
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Spiro[Azetidine‐3,3′‐Indoline]‐2,2′‐Diones via Copper(I)‐Catalyzed Kinugasa/C−C Coupling Cascade Reaction

Abstract: Spiro[azetidine-indolines] are important scaffolds in diverse bioactive compounds. Current efforts to synthesize spiro[azetidine-indolines] are limited to chiral spiro[azetidine-2,3'-indolines]. Asymmetric synthesis of structurally similar chiral spiro[azetidine-3,3'-indolines] remains unexplored. In this work, the first copper(I)catalyzed asymmetric Kinugasa/aryl CÀ C coupling cascade reaction is described. This provides a straightforward access to densely functionalized chiral spiro[azetidine-3,3'-indoline]-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Spiro­[azetidine-indoline] is an important scaffold for various bioactive compounds, but current efforts to synthesize spiro­[azetidine-indolines] are mostly limited to chiral spiro­[azetidine-2,3′-indolines] . As asymmetric synthesis of structurally similar spiro­[azetidine-3,3′-indolines] remains unexplored, Cai and co-workers discovered the first Cu-catalyzed asymmetric Kinugasa/aryl C–C coupling cascade reaction to address this problem . The team utilized the organo-Cu (I) intermediate generated in situ from the asymmetric Kinugasa reaction of N -(2-iodo-aryl)-propiolamides and nitrones, followed by intramolecular aryl C–C coupling (Scheme ).…”
Section: Recent Reports On Cu-catalyzed Reactionsmentioning
confidence: 99%
“…Spiro­[azetidine-indoline] is an important scaffold for various bioactive compounds, but current efforts to synthesize spiro­[azetidine-indolines] are mostly limited to chiral spiro­[azetidine-2,3′-indolines] . As asymmetric synthesis of structurally similar spiro­[azetidine-3,3′-indolines] remains unexplored, Cai and co-workers discovered the first Cu-catalyzed asymmetric Kinugasa/aryl C–C coupling cascade reaction to address this problem . The team utilized the organo-Cu (I) intermediate generated in situ from the asymmetric Kinugasa reaction of N -(2-iodo-aryl)-propiolamides and nitrones, followed by intramolecular aryl C–C coupling (Scheme ).…”
Section: Recent Reports On Cu-catalyzed Reactionsmentioning
confidence: 99%
“…Cai and coworkers reported a copper-catalyzed interrupted asymmetric Kinugasa reaction of N -(2-iodo-aryl)-propiolamides and nitrones to obtain spirocyclic β-lactams. 58 In this example, an intramolecular aryl C–C coupling reaction was employed in order to trap the copper intermediate formed in the Kinugasa reaction.…”
Section: Metal-assisted Synthesismentioning
confidence: 99%
“…L3 was less effective at delivering high enantionduction (Table , entry 3). We continued our investigation by exploring the BOX series of ligands employed by others in asymmetric Kinugasa/electrophilic substitution reactions. , Using benzyl-substituted SaBOX-1 , 3a was formed in 90:10 er (Table , entry 4). Other substitution patterns were shown to improve both yield and selectivity (entries 5–7).…”
mentioning
confidence: 99%
“…Enders et al in 2018 reported the first example of a Kinugasa/cyclization cascade using a tethered electrophile, which formed complex products from the intermolecular reaction of nitrones and alkyne-tethered cyclic enones (Scheme C) . Recently, another intramolecular Kinugasa cyclization was reported using aryl iodide-tethered alkynes by the Cai group (Scheme D) . The Xu laboratory has explored the use of exogenous electrophiles in thiolation and allylation approaches but in noncyclization cascades …”
mentioning
confidence: 99%